Analysis of Employee Recruitment in Improving Performance in the Accommodation Service Business - Muhammad Yusuf (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
The economic development of a region, especially in the development of the tourism sector, cannot be separated from the development of its human resources. This study aims to see the employee recruitment system, employee performance, and employee education qualifications at hotels in the city of Parepare. 7 informants are leaders and/or employees who are taken from hotels who are deemed to be able to represent the whole hotel in Parepare City. This research is applied research with a qualitative approach. Data were analyzed descriptively. Observations were made at seven hotels as the object of research, one of which recruited employees openly, while the other six hotels did not. Of all employees in the seven hotels, only a small proportion have educational qualifications with a tourism background. There is one hotel that has employees with a tourism education background, but only at the level of vocational high school education, besides that employee performance is generally still low in almost all hotels, only one hotel which according to our observations is quite good in terms of hotel service standards. The results showed that the recruitment system has not been implemented openly, employee performance is still low and educational qualifications are not following the needs of the workforce in the hotel industry